2015
DOI: 10.5267/j.ijiec.2014.9.001
|View full text |Cite
|
Sign up to set email alerts
|

Two-warehouse inventory model for deteriorating items with price-sensitive demand and partially backlogged shortages under inflationary conditions

Abstract: In today's competition inherited business world, managing inventory of goods is a major challenge in all the sectors of economy. The demand of an item plays a significant role while managing the stock of goods, as it may depend on several factors viz., inflation, selling price, advertisement, etc. Among these, selling price of an item is a decisive factor for the organization; because in this competitive world of business one is constantly on the lookout for the ways to beat the competition. It is a well-known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“… The demand rate D(b, Q,θ) is a function of selling price b and the quality parameter Q (Q defines the effect of quality on the item demand: Q > 0) (Jaggi et al 2015 ; Yang et al 2020 ) as shown in Fig. 2 .…”
Section: Assumptions and Notationsmentioning
confidence: 99%
See 1 more Smart Citation
“… The demand rate D(b, Q,θ) is a function of selling price b and the quality parameter Q (Q defines the effect of quality on the item demand: Q > 0) (Jaggi et al 2015 ; Yang et al 2020 ) as shown in Fig. 2 .…”
Section: Assumptions and Notationsmentioning
confidence: 99%
“…This section explains the change in average profit caused due to demand disruption. The input parameters provided here has been derived from the past literature works of (Jaggi, et al 2015 ; Rana et al 2021a ; Mishra et al 2020 ).…”
Section: Mathematical Model Developmentmentioning
confidence: 99%
“…In current competitive business environments keeping good inventories appropriately has become a key challenge for most industries (Jaggi et al, 2015) and this requires a careful warehouse design and management. Automated Storage and Retrieval Systems (AS/RSs) are warehousing systems widely applied to both distribution and production settings, especially in case of a large amount of products to store and high throughput rates.…”
Section: Introductionmentioning
confidence: 99%
“…Singh and Rathore (2014) developed an inventory model for deteriorating item with reliability consideration and trade credit. Jaggi et al (2015) come forward with two-warehouse inventory model for deteriorating items with price sensitive demand and partially backlogged shortages under inflationary environment conditions. After that Tayal et al (2015) presented a production inventory framework for non-instantaneous deteriorating items with time dependent holding cost and exponential demand rate.…”
Section: Introductionmentioning
confidence: 99%